The role of sampling methodology and site selection on myxomycete data from the Neotropics - Rojas Alavarado, Carlos Alonso (2022)
Myxomycete sporocarps are practical units that can be used to study the effect of environmental issues such as climate change, urbanization, and natural disasters on microorganisms. Recent scientific literature lacks empirical approaches to understand the impacts of sampling design and site selection on the data obtained in myxomycete field surveys. The present investigation was designed to generate useful data for the evaluation of methodological approaches. Myxomycetes were studied for two years in a tropical premontane wet forest in Costa Rica using two different sampling strategies and several collecting sites to evaluate potential differences in the results. Field collections were used to generate the dataset due to their usefulness for monitoring purposes. Sampling strategies had a smaller impact on the reported structure and composition of obtained species assemblages than site selection, but a combination of both clearly maximized the effort and provided the best results during the field surveys. Functional variables of the forest with direct influence on the myxomycete life cycle such as tree diameter and leaf litter depth impacted the results synergically. Simulations of surveys at two different levels of effort were compared with total yearly efforts and results showed that revisiting sampling sites maximized the field effort. Results demonstrated that the variability of sporocarp production in tropical forests should be considered in the design of long-term field experiments on myxomycetes.